NiAl Layered Double Hydroxide Flowers with Ultrathin Structure Grown on 3D Graphene for High‐Performance Supercapacitors. Issue 32 (14th August 2019) - Guo, Xingmei; Liu, Huili; Xue, Yanchun; Chen, Jiale; Wan, Xiaohan; Zhang, Junhao; Liu, Yuanjun; Yuan, Aihua; Kong, Qinghong; Fan, Hai
Abstract : To overcome the low electrical conductivity weakness of layered double hydroxide and to improve the electrochemical energy storage performance as supercapacitor electrodes, NiAl layered double hydroxide (NiAl‐LDH) flowers with ultrathin structure grown on three‐dimensional graphene (3DG) was constructed via a facile hydrothermal strategy. The NiAl‐LDH/3DG composites as binder‐free supercapacitor electrode showed a high specific capacitance of 884.5 F g –1 at 1 A g –1 . Excellent cycle stability retaining 90 % of the initial capacitance after 7000 cycles at 5 A g –1 was also demonstrated, with the coulombic efficiency stayed above 95 % during the whole cycling process. The excellent performances should be ascribed to the synergistic effect of NiAl‐LDH and 3DG, in which the NiAl‐LDH ultrathin nanoflake petals provide sufficient pseudocapacitive sites; while 3DG provides robust and highly interconnected skeleton for efficient mass/charge transport. Abstract : NiAl layered double hydroxide flowers grown on three‐dimensional graphene was fabricated, which showed a high specific capacitance of 884.5 F g – 1 at 1 A g – 1 . Good cycling stability retaining 90 % of the initial capacitance after 7000 charge/discharge cycles at 5 A g – 1 was also demonstrated, while the coulombic efficiency stayed above 95 % during the whole cycling process.